Post‐Myocardial Infarction T‐tubules Form Enlarged Branched Structures With Dysregulation of Junctophilin‐2 and Bridging Integrator 1 (BIN‐1). Issue 5 (May 2017) - Pinali, Christian; Malik, Nadim; Davenport, J. Bernard; Allan, Laurence J.; Murfitt, Lucy; Iqbal, Mohammad M.; Boyett, Mark R.; Wright, Elizabeth J.; Walker, Rachel; Zhang, Yu; Dobryznski, Halina; Holt, Cathy M.; et al.
Abstract : Background: Heart failure is a common secondary complication following a myocardial infarction (MI), characterized by impaired cardiac contraction and t‐tubule (t‐t) loss. However, post‐MI nano‐scale morphological changes to the remaining t‐ts are poorly understood. Method and Results: We utilized a porcine model of MI, using a nonlethal microembolization method to generate controlled microinfarcts. Using serial block face scanning electron microscopy, we report that post‐MI, after mild left‐ventricular dysfunction has developed, t‐ts are not only lost in the peri‐infarct region, but also the remnant t‐ts form enlarged, highly branched disordered structures, containing a dense intricate inner membrane. Biochemical and proteomics analyses showed that the calcium release channel, ryanodine receptor 2 (RyR2), abundance is unchanged, but junctophilin‐2 (JP2), important for maintaining t‐t trajectory, is depressed (−0.5×) in keeping with the t‐ts being disorganized. However, immunolabeling shows that populations of RyR2 and JP2 remain associated with the remodeled t‐ts. The bridging integrator 1 protein (BIN‐1), a regulator of tubulogensis, is upregulated (+5.4×), consistent with an overdeveloped internal membrane system, a feature not present in control t‐ts. Importantly, we have determined that t‐ts, in the remote region, are narrowed and also contain dense membrane folds (BIN‐1 is up‐regulated +3.4×), whereas the t‐ts have a radial organization comparable to control JP2 is upregulated +1.7×. Conclusions: This study reveals previously unidentified remodeling of the t‐t nano‐architecture in the post‐MI heart that extends to the remote region. Our findings highlight that targeting JP2 may be beneficial for preserving the orientation of the t‐ts, attenuating the development of hypocontractility post‐MI.